Thin film solar cell modelling and simulation - 262770 Hasbullah Anthony Hasbi; Samsudi Sakrani, supervisor; Fakulti Sains (2002)
Project Paper (Bachelor of Industrial Science (Physics)) - Universiti Teknologi Malaysia, 2002